2009
DOI: 10.1111/j.1365-3083.2009.02340.x
|View full text |Cite
|
Sign up to set email alerts
|

Review: To What Extent are T Cells Tolerant to Immunoglobulin Variable Regions?

Abstract: Id-specific B cells recognize conformational determinants on complete Ig-moleculesImmunoglobulin V-regions are extremely diversified due to V(D)J recombination and somatic hypermutation [1]. Thus, immunoglobulin V-regions probably represent the largest collection of diverse antigenic determinants on self molecules within the body. B cell recognition of such Id determinants depend on association of L-and H-chain V-regions, which enormously increases the number of serological Id determinants expressed on Ig mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 53 publications
0
32
1
Order By: Relevance
“…[33][34][35][36] In these models, idiotype-specific T cells recognize preferentially unique epitopes from complementarity-determining region or generated through somatic hypermutation, whereas the natural T-cell receptor repertoire is considered tolerant toward germline-encoded immunoglobulin sequences. 37 We have recently demonstrated that T regulatory cells (Tregs) appear to play an important role in the suppression of effector T cells with specificity for framework region epitopes. 38 In accordance with these animals studies, the Poisson regression analyses of the ELISpot results in our consecutive trials, 10 and our in vitro experiments with idiotype-transfected surrogate target cells 19 suggest that vaccination-induced T-cell activity is directed predominantly against individual rather than shared idiotype peptides.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] In these models, idiotype-specific T cells recognize preferentially unique epitopes from complementarity-determining region or generated through somatic hypermutation, whereas the natural T-cell receptor repertoire is considered tolerant toward germline-encoded immunoglobulin sequences. 37 We have recently demonstrated that T regulatory cells (Tregs) appear to play an important role in the suppression of effector T cells with specificity for framework region epitopes. 38 In accordance with these animals studies, the Poisson regression analyses of the ELISpot results in our consecutive trials, 10 and our in vitro experiments with idiotype-transfected surrogate target cells 19 suggest that vaccination-induced T-cell activity is directed predominantly against individual rather than shared idiotype peptides.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The available in silico tools permit only limited analyses for human MHC class II. Therefore, our study had to focus on HLA class I.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 These findings are in accordance with animal studies demonstrating T-cell tolerance for germlineencoded immunoglobulin sequences but responsiveness to novel idiotopes arising from junctional diversity or somatic mutations. 10 Because mouse models have also shown T cell-mediated immunosurveillance against hypervariable idiotypic peptides, 11 we sought to obtain evidence that spontaneous idiotype-directed T-cell immunity is operational in nonimmunized lymphoma patients and impairs expansion of malignant B-cell clones that express an idiotype with high immunogenicity. To test this hypothesis, we performed a "reverse immunology" bioinformatics study in 39 FL patients.…”
Section: Introductionmentioning
confidence: 99%
“…23 Antibody humanization pursues the complementary goals of increasing acceptability to the immune system while maintaining stability, specificity, and affinity. In general, humanization relies on the fact that the human immune system is relatively tolerant of human antibodies, 24 and that antibodies of any given isotype have similar modular structure and sequence-structure-function relationships. For example, standard grafting-based humanization techniques leverage antibody structural modularity to incorporate key functional parts of the exogenous antibody on a human antibody framework, with the aim of maximizing the human portion of the antibody while maintaining antigen binding.…”
Section: Introductionmentioning
confidence: 99%